Optimalisasi Pengelolaan Lingkungan Hidup di Kota Padang Panjang: Tantangan dan Strategi Pengelolaan Sampah, Air Bersih, dan Ruang Terbuka Hijau - Syamsir, Syamsir; Salsabilla, Dea; Siska, Siska; Aftaviani, Yosa; Erita, Zahara (Innovative: Journal Of Social Science Research, 2024)
Padang Panjang City faces various environmental challenges involving waste management, clean water distribution, and decreasing the quality of green open space (RTH). This article aims to identify these main problems and propose optimal environmental management strategies. The increase in waste volume due to population growth requires an integrated recycling and management approach, while the unequal distribution of clean water requires infrastructure improvements and education regarding domestic and industrial waste management. On the other hand, the decline in green open space use threatens the balance of urban ecosystems, requiring regulatory enforcement initiatives and community participation to maintain its sustainability. Based on literature analysis and interviews with related agencies, this article offers practical strategies to overcome these three issues through a collaborative approach between government, society and the private sector. It is hoped that consistent implementation of this strategy will be able to improve the quality of the environment in Padang Panjang City and improve the welfare of its people.